Technology Is a "Blessing and a Curse": The Perceived Risks and Benefits of Digital Technology Adoption at Domestic Violence Organizations that Serve Teens. Issue 1 (2nd January 2023) - Storer, Heather L.; Scott, Carol F.; Rodriguez, Maria; Nyerges, Eva X.
Abstract: Despite the promise of digital technologies to strengthen social work practice, like many other social service organizations, service providers at domestic violence (DV) and sexual assault (SA) organizations have yet to fully embrace their use in their work. Our study explores teen dating violence (TDV) service providers' perceptions of both the benefits and the risks of using digital technologies in their service delivery system. We conducted in-depth qualitative interviews with TDV staff at agencies throughout the United States (N = 35). Findings suggest service providers are actively negotiating the ways technology can nurture their clients' safety or perpetuate harm including exacerbating the digital divide. DV service providers contend that while technology can be lifesaving, important considerations must address associated harms.